Estimation of eigenvalues of self-adjoint operators - Yavorskii, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Estimates of the number of eigenvalues are obtained for perturbations of certain selfadjoint and unitary operators in a Hilbert space. As a special case, we consider a perturbation of the operator of multiplication by an independent variable in $L_2(\mathbb{R})$ and $L_2(0, 1)$.